2009
DOI: 10.1021/ol9025815
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Tunable, and Efficient Chiral Bisdihydrobenzooxaphosphole Ligands for Asymmetric Hydrogenation

Abstract: A series of novel, efficient, air-stable, and tunable chiral bisdihydrobenzooxaphosphole ligands (BIBOPs) were developed for rhodium-catalyzed hydrogenations of various functionalized olefins such as alpha-arylenamides, alpha-(acylamino)acrylic acid derivatives, beta-(acylamino)acrylates, and dimethyl itaconate with excellent enantioselectivities (up to 99% ee) and reactivities (up to 2000 TON).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 28 publications
(5 reference statements)
2
73
0
Order By: Relevance
“…Fully aware of the challenges associated with the asymmetric hydrogenation of tetrasubstituted olefins, 9 we aspired to engineer a new catalytic system for this important transformation by leveraging our recently developed dihydrobenzooxaphosphole (BOP)-based ligand series ( vide infra ). 10,11 To access requisite hydrogenation precursor A , a conceptually concise sequence was devised involving an S N Ar coupling of fragments 4 and 5 followed by an intramolecular C–H arylation. At the outset, the proposed cyclization to the C-3 position of pyridine was expected to be challenging, with few related examples found in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fully aware of the challenges associated with the asymmetric hydrogenation of tetrasubstituted olefins, 9 we aspired to engineer a new catalytic system for this important transformation by leveraging our recently developed dihydrobenzooxaphosphole (BOP)-based ligand series ( vide infra ). 10,11 To access requisite hydrogenation precursor A , a conceptually concise sequence was devised involving an S N Ar coupling of fragments 4 and 5 followed by an intramolecular C–H arylation. At the outset, the proposed cyclization to the C-3 position of pyridine was expected to be challenging, with few related examples found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group has reported a highly modular dihydrobenzooxaphosphole (BOP) core for ligand design. 10 Many effective ligands have been derived from this motif and have been found to mediate a variety of different catalytic transformations. 11 In particular, the rigid bidentate BoQPhos P,N-ligands, which were constructed from the BOP core by anchoring a less basic nitrogen-containing pyridine fragment onto the carbon atom of the O,P ring system (see Figure 4), have been successfully demonstrated for asymmetric hydrogenation of nonfunctionalized tri- and tetrasubstituted olefins.…”
Section: Resultsmentioning
confidence: 99%
“…Many examples can be found in the literature for the resolution of 3 cyclic P-chiral phosphines, phosphine oxides and phosphonium salts via the formation of covalent diasteromers [11][12][13], diastereomeric coordination [14][15][16][17][18][19], molecular complexes [10,20,21] or diastereomeric salts [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the synthesis of a few optically active P-chiral heterocyclic ligands was described and the transition metal complexes of these P(III)-compounds were used as catalysts mainly in enantioselective hydrogenation reactions [11,13,16,18,21,[28][29][30][31][32]. There are only a few examples for P-heterocyclic ligands that were used in hydroformylation [5].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenations were conducted at room temperature at a hydrogen pressure of 300 psi for 12 h. It was found that well-known chiral ligands such as BINAP, Josiphos, and Tangphos [8] did not provide superb enantioselectivities (Table 1, entries 1-2). Ligand BIBOP (L1), which was highly effective for hydrogenation of a-aryl-N-acetyl enamides in our previous study, [14] proved to be inefficient (Table 1, entry 3). A low ee was also observed when MeO-BIBOP (L2) was applied ( Table 1, entry 4).…”
mentioning
confidence: 96%